"The Most Valuable Means of Extinguishing the Destroying Fires": Fire-fighting and the London Water Companies in the Long Eighteenth Century. (2nd January 2017) - van Lieshout, Carry
Abstract : This paper evaluates the role of London's water companies in organized fire-fighting in the long eighteenth century. It sets out the extent to which the companies' directors were willing to go to provide free water in cases of fire, and questions their motivations in providing this free public service. While legal reasons played a role, the paper argues that the directors' motivation can also be attributed to a combination of local interests, charity, and the positive publicity generated by their efforts. This publicity both bolstered the reputation of the several competing water companies, and reflected positively on the directors in charge.